Child task-supported interaction in the Spanish EFL setting. Research and challenges - García Mayo, María del Pilar (International Journal of English Studies, 2018)
Task-based language teaching research has expanded substantially in foreign language (FL) contexts but most research studies have been carried out with young adults in university settings, despite the fact that FL programs for children are on the increase worldwide. However, there is a clear lack of research-based evidence of what children actually do while performing tasks, which is crucial in order to make decisions about appropriate educational provision, to inform policy makers, and to maximize children’s learning opportunities. This paper focuses on current research on children in task-supported programs both in mainstream English as a Foreign Language (EFL) and Content and Language Integrated Learning (CLIL) contexts. It reviews studies carried out within interactional and sociocultural frameworks and shows how children successfully negotiate to make language meaningful, how they engage with the tasks and how they collaborate in different ways during task performance. Challenges and future research directions will be highlighted.